Electrochemical and Thermodynamic Study of Septrin and Flagyl as Corrosion Inhibitors for Mild Steel in Acidic Media - Samuel Batet, Benjamin Ufuoma Oreko, Silas Oseme Okuma, Stanley Okiy (NIPES - Journal of Science and Technology Research, 2025)
Corrosion of mild steel in acidic media is a significant issue in industrial applications, leading to material degradation and increased maintenance costs. This study investigates the corrosion inhibition properties of Septrin (Co-trimoxazole) and Flagyl (Metronidazole) for mild steel in 2 M HCl, with the aim of finding alternative, cost-effective inhibitors. These drugs were selected due to their potential anticorrosion properties, with limited research available on their inhibitory efficiency in acidic environments. The study was conducted over a temperature range of 303 K to 363 K, with inhibitor concentrations varying from 25 g/L to 75 g/L. Both drugs exhibited promising corrosion inhibition, with Flagyl showing superior performance. The adsorption of both inhibitors followed the Langmuir and Freundlich isotherms, indicating a physisorption mechanism. Gibbs free energy calculations confirmed the spontaneity and stability of the adsorption process, with Septrin showing ΔG_ads values of -19.13 kJ/mol at 303 K and -22.91 kJ/mol at 363 K, while Flagyl showed -16.46 kJ/mol at 303 K and -19.72 kJ/mol at 363 K. Electrochemical tests revealed that Flagyl reduced the corrosion rate from 149.35 mm/year to 60.02 mm/year at a concentration of 75 g/L, while Septrin reduced it to 78.53 mm/year, resulting in inhibition efficiencies of 59.8% and 47.4%, respectively. Thermodynamic analyses indicated an increase in activation energy in the presence of both inhibitors. Scanning Electron Microscopy (SEM) and Energy Dispersive X-ray (EDX) analyses showed that both inhibitors improved the surface conditions of mild steel, with Flagyl being the more effective inhibitor. Future research should focus on evaluating the long-term stability of these inhibitors in corrosive environments.
The assessments of Septrin and Flagyl as Corrosion inhibitors in an acidic medium for mild steel structure.
Keywords: Corrosion; Inhibitive Drugs; Kinectic and Thermodynamic Assessments; Petrochemical Plants